Human Resource Development through Knowledge Management Towards Digital Transformation System - Wijayadne, Devi Rahnjen (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
This ponder points to get it how Computerized Change frameworks can be actualized within the setting of Human Asset Advancement and Information Administration. It incorporates the consideration of the innovations and apparatuses utilized in Advanced Change. Another objective is to investigate how Information Administration and Advanced Transformation can work together to attain organizational objectives. This investigation is based on the Precise Writing Audit (SLR). Through this strategy, analysts collect a few multidisciplinary distributions from cited and high-device multidisciplinary journals. Therefore, for our consider, taking these critical components into consideration, we see SLR as a reasonable strategy that combines these components whereas avoiding analyst predisposition. Based on the comes about of the writing consider gotten, Computerized Transformation has empowered organizations to utilize innovation in overseeing information, which in turn, makes a difference within the advancement of Human Assets. Innovation has encouraged the collection, capacity, and sharing of knowledge, which is a vital perspective of Information Administration. Be that as it may, considers moreover appear that there are challenges within the application of innovation in Information Administration. A few of these challenges may incorporate resistance to alter, need of understanding of unused innovations, and information security issues. Hence, it is vital for organizations to address these challenges to guarantee effective usage of Computerized Change and Information Administration. By and large, the comes about appear that Advanced Change and Knowledge Administration are key variables in Human Asset hones and organizational learning. In any case, it is vital for organizations to address challenges which will emerge amid this handle to guarantee their victory.